“We are like a family!”: Flexibility and Intention to Stay in Boutique Hotels in Turkey - Unsal-Akbıyık, Banu; Zeytinoglu, Isik (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
This study focuses on a unique type of small business—boutiquehotels in Istanbul, Turkey—, and aims to understand whetheremployers’ use of internal flexibility strategies is associatedwith boutique hotel employees’ intention to stay in theirorganization. Internal flexibility strategies refer to shiftwork, longworkweeks, unpaid overtime, and working preferred hours.Our study focuses on the experience of employees in boutique hotels in Turkey, which is one of the largest economies globally with its hospitality sector being the eighth largest in the world (Zeytinoglu et al., 2012a and 2012b). We test the conceptual model of internal flexibility strategies and intention to stay using data from 20 interviews and 122 surveys with employees in 32 boutique hotels.As our qualitative and quantitative study shows, shiftwork decreasesboutique hotel employees’ intention to stay, but long workweeksand working unpaid overtime do not affect the intention to stay.Furthermore, as our qualitative study shows, the close family-like workenvironments that exist in boutique hotels contribute to theemployees’ intention to stay. As our respondents said in thequalitative part of the study: “‘We’re like afamily!’ and cannot leave our ‘home’!”, despitenot liking the shiftwork.By examining the relationships between flexibility and intention tostay in small workplaces such as boutique hotels, our study contributesto both the academic literature on internal labour flexibility and tothe model of intention to stay. For practitioners, this study providesevidence on the use of the type of internal labour flexibilitystrategies used in boutique hotels, contributing to the understandingof how boutique hotels can be successful in retaining valuable staff.